The Impact of Financial Literacy, Financial Education, Socioeconomic Status, and Lifestyle on Personal Financial Management Among Generation Z in Pekanbaru - Norfadila, Saptina (Insight Management and Business (IMB), 2024)
This study aims to identify the influence of financial literacy, financial education, socioeconomic status, and lifestyle on personal financial management among Generation Z in Pekanbaru. Data were collected through a survey using questionnaires distributed to 210 respondents and analyzed using multiple linear regression with SPSS version 25. The results show that financial literacy and financial education have a positive and significant impact on personal financial management, indicating that higher levels of literacy and education lead to better financial management skills. Socioeconomic status also has a positive and significant influence, suggesting that individuals with higher socioeconomic status tend to have better financial management capabilities. Conversely, lifestyle has a negative and significant impact, where Generation Z in Pekanbaru tends to have a hedonistic lifestyle that adversely affects their financial management. The implications of this study emphasize the importance of enhancing financial literacy and education, as well as understanding the negative effects of a hedonistic lifestyle, to ensure that Generation Z manages their finances more wisely.